Vertical integrated service model: an educational intervention for chronic disease management and its effects in rural China - a study protocol - Shaofan Chen; Bo Burström; Vibeke Sparring; Dongfu Qian (BMC, 2018)
Abstract Background Chronic diseases are becoming a huge threat to the Chinese health system. Although the New Round of Medical Reform aims to improve this, the chronic disease management in rural China is still worrying as it relies highly on hospital care instead of primary care. The vertical integrated care model has proven to be effective for chronic disease patients in many high-income countries, while few studies have been conducted in China. In this project, vertical integrated care will be applied to optimize the care of patients with type 2 diabetes mellitus (T2DM) and primary hypertension in rural China, and to shift the care from hospital to primary care. Methods An educational intervention was conducted in three pilot counties in Jiangsu province, a high-income province in southeast China. The intervention was based on the model of vertical integrated care between the three-levels of healthcare institutions. In the pilot counties, 22 townships were included (11 in the intervention and control groups, respectively). Service teams assembled by the local health bureaus implemented the intervention which provides services for both patients and healthcare professionals. Questionnaire interviews (n = 4259) and medical records were used to collect patient data (physiological measures, health-related quality of life, satisfaction with care). Data from healthcare professionals (n = 282) was gathered through questionnaires and in-depth interviews (knowledge about chronic diseases, general procedure of diagnosing and registering, chronic disease management situation, perceptions of chronic disease treatment and prevention). Baseline data were collected before the start of the intervention in Nov 2015, follow-up data in Oct-Nov 2016, and final data completed in Jul-Aug 2017. Discussion The intervention has been conducted smoothly and gotten support from patients, healthcare institutions and local health authorities. The research team anticipates that the vertical integrated model will improve patients' health, satisfaction with care, and their understanding of their chronic disease. We also anticipate that healthcare professionals can acquire more information about chronic diseases and improve their strategy for providing good quality care for patients. Trial registration ISRCTN13319989 Registration date: 4th April, 2017.